2019
DOI: 10.2337/dc20-s014
|View full text |Cite
|
Sign up to set email alerts
|

14. Management of Diabetes in Pregnancy:Standards of Medical Care in Diabetes—2020

Abstract: The American Diabetes Association (ADA) "Standards of Medical Care in Diabetes" includes the ADA's current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee (https://doi.org/10.2337/dc20-SPPC), are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(160 citation statements)
references
References 106 publications
0
156
0
4
Order By: Relevance
“…Dalfra et al 33 found that diet therapy alone can improve GV in pregnant women with GDM. The 2020 ADA guidelines 55 specify that a good lifestyle (diet control and proper exercise) is an important part of GDM management. About 70%-85% of women diagnosed with GDM can control postprandial hyperglycemia and reduce GV by simply changing lifestyles, which can meet the treatment needs of many women.…”
Section: Controlling Gvmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalfra et al 33 found that diet therapy alone can improve GV in pregnant women with GDM. The 2020 ADA guidelines 55 specify that a good lifestyle (diet control and proper exercise) is an important part of GDM management. About 70%-85% of women diagnosed with GDM can control postprandial hyperglycemia and reduce GV by simply changing lifestyles, which can meet the treatment needs of many women.…”
Section: Controlling Gvmentioning
confidence: 99%
“…Reasonable insulin treatment can help make the blood glucose of patients with gestational diabetes stable to reach the standard. 55 However, unreasonable insulin application may increase the risk of hypoglycemia, including not properly adjusting insulin doses, not monitoring and adjusting the insulin dose in a timely manner, and not receiving sufficient health education. Therefore, in clinical practice, it is necessary to carry out health education for patients and guide patients to monitor blood glucose on a timely basis and adjust insulin dosage to avoid blood glucose fluctuations caused by hypoglycemia.…”
Section: Controlling Gvmentioning
confidence: 99%
“…At present, the guidelines of various diabetes associations worldwide all mention ketosis in the management of gestational diabetes, but the focuses are different (The specific content is shown in Table 1). [32][33][34][35] Among them, the guidelines of the American Diabetes Association, the American College of Obstetricians and Gynecologists, and the Joint British Diabetes Societies focus more on the prevention of diabetic acidosis, while the International Federation of Obstetrics and Gynecology and the Chinese Diabetes Society focus more on the relationship between the diet control and the occurrence of starvation ketosis to discuss the monitoring of ketone bodies.…”
Section: Recommendations Of Various Guidelines For Monitoring Ketone mentioning
confidence: 99%
“…Para las pacientes insulinorrequirientes se plantean metas en ayunas <95 mg/dL y posprandiales <120 mg/dL. 42 Teniendo en cuenta esto, ¿una meta más estricta favorece menores desenlaces cardiovasculares y obstétricos?…”
Section: Metas Glicémicasunclassified